Lage und Entwicklung ausgewählter Fischbestände: Einschätzung des ICES im Juni 2002 - Hammer, Cornelius; Gröhsler, Tomas; Zimmermann, Christopher (2002)
During the spring session of the ICES Advisory Committee for Fisheries Management (ACFM) the stocks of the Northern Pelagic and Blue Whiting, North Western, Baltic, Arctic and Deep Sea Working Groups have been analysed and assessed, as well as the Nephrops stocks. As in previous years ICES recommends a reduction in fishing mortality for a number of stocks. Moreover, ICES recommends for many stocks to establish recovery and management plans, to safeguard a continuous development of the stocks towards safe biological limits. Detailed recovery plans were proposed for cod and hake in the North Sea. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery Research in 2010.